2015
DOI: 10.1016/j.nedt.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Educating registered nursing and healthcare assistant students in community-based supportive care of older adults: A mixed methods study

Abstract: Collaborative education for nursing and healthcare assistant students can enhance self-perceived knowledge and competence in supportive care of adults with advanced chronic illness. An innovative clinical experience can maximize reciprocal learning while providing nursing services to a population that is not receiving home-based care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Most authors used a pre‐test/post‐test design to measure outcomes (Table ). Changes in system or organizational policies were assessed in five studies; patient outcomes were assessed in only one study (Pesut, McLean, et al, ). Sustainability of knowledge gains or sustainability of skills put into practice was measured in five studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most authors used a pre‐test/post‐test design to measure outcomes (Table ). Changes in system or organizational policies were assessed in five studies; patient outcomes were assessed in only one study (Pesut, McLean, et al, ). Sustainability of knowledge gains or sustainability of skills put into practice was measured in five studies.…”
Section: Resultsmentioning
confidence: 99%
“…Most authors reported what the participants perceived as outcomes for patients and families. Patients were recruited as informants in only one study (Pesut, McLean, et al, ). Changes to patient and family related policies were a direct result of the educational intervention in two other studies (Curry et al, ; Phillips et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gaberson et al (2015) described the benefits to the community as having control over the service provided and the recipients of service becoming better able to serve themselves and be served by their own actions. In a project that involved nursing students conducting home visits with people with chronic life-limiting conditions, clients reported they learnt from the students and benefited from their visits (Pesut et al, 2015). Benefits to students included the development of skills in communication, critical thinking, and collaboration.…”
Section: Introductionmentioning
confidence: 99%